Ennahdha et les salafistes : la construction relationnelle de la « modération » - Théo Blanc (L’Année du Maghreb)
A governing Islamist party, Ennahdha seems to perfectly fit the model predicted by the moderation theory according to which political inclusion generates ‘moderate’ actors. This article proposes to go beyond the institutionalist lens of the inclusion-moderation theory and the asymmetrical approach of the cooperation-moderation theory by pointing out how Ennahdha’s moderation was articulated in a double pressure between secular actors and radical Islamic actors (Salafis). The argument, in line with the “moderation through exclusion” theory (Cavatorta and Merone, 2013), shows that (1) Ennahdha’s moderation largely preceded inclusion, (2) the cooperation-moderation dynamic with Nidaa Tounès was based on the exclusion of the ‘radicals’ and (3) the moderation theory does not apply to the party’s social platform. Accordingly, Ennahdha’s moderation defined as the acceptation of a civil democratic system consisted neither in a mere strategic adjustment following inclusion nor in an inclusive process exerting a centripetal force on the Islamic field turning ‘radicals’ into ‘moderate’, but rather in a centrifugal process pushing ‘radicals’ away.